2014
DOI: 10.3390/ijms150711387
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Antioxidant Assays for Biological Samples Based on the Reduction of Copper Complexes—The Importance of Analytical Conditions

Abstract: Total antioxidant capacity assays are recognized as instrumental to establish antioxidant status of biological samples, however the varying experimental conditions result in conclusions that may not be transposable to other settings. After selection of the complexing agent, reagent addition order, buffer type and concentration, copper reducing assays were adapted to a high-throughput scheme and validated using model biological antioxidant compounds of ascorbic acid, Trolox (a soluble analogue of vitamin E), ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 44 publications
1
30
1
1
Order By: Relevance
“…It is possible that the presence of lactate and formate in LA and FA‐hydrolysates, respectively are responsible for interference with the FRAP assay. Marques et al reported that buffer systems significantly influence results in a Cu(III)‐reducing assay (Marques, Magalhães, Tóth, & Segundo, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the presence of lactate and formate in LA and FA‐hydrolysates, respectively are responsible for interference with the FRAP assay. Marques et al reported that buffer systems significantly influence results in a Cu(III)‐reducing assay (Marques, Magalhães, Tóth, & Segundo, ).…”
Section: Resultsmentioning
confidence: 99%
“…Total antioxidant capacity (TAC) is the measure of the amount of free radicals scavenged by a test solution [35], and it is used to evaluate the antioxidant capacity of biological samples [36]. Total antioxidant capacity (TAC) includes both enzymatic antioxidants, such as catalase, and non-enzymatic antioxidants, such as ascorbic acid [37].Studies on total antioxidant capacity in albino rats administered with V. amygdalina and G. latifolium extracts following diabetic induction is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the interaction of thiols with reactive radicals can generate thiyl radicals which have a pro-oxidant effect, especially in iron-rich environments, which is the case of iron atoms release during Mb autoxidation [27]. However, reduced glutathione represents a powerful endogenous antioxidant as demonstrated by other antioxidant assays that applied different mechanisms of reaction such as metal reduction [28] and scavenging of multiple reactive oxygen species [29].…”
Section: Evaluation Of Analytical Conditions Of Myoglobin Microplatementioning
confidence: 98%